2001
DOI: 10.1073/pnas.021535398
|View full text |Cite
|
Sign up to set email alerts
|

A peripheral marker for schizophrenia: Increased levels of D3 dopamine receptor mRNA in blood lymphocytes

Abstract: Dopamine is a major neurotransmitter in the central nervous system, and its receptors are associated with a number of neuropathological disorders such as Parkinson's disease and schizophrenia. Although the precise pathophysiology of schizophrenia remains unknown, the dopaminergic hypothesis of the illness assumes that the illness results from excessive activity at dopamine synapses in the brain. Because, at present, the diagnosis of schizophrenia relies on descriptive behavioral and symptomatic information, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
3
5

Year Published

2001
2001
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(105 citation statements)
references
References 9 publications
5
92
3
5
Order By: Relevance
“…In the peripheral lymphocytes of schizophrenia patients, significantly increased mRNA expression of D2 and D3 receptors (Kwak et al 2001;Ilani et al 2001;Zvara et al 2005) and reduced gene expression of dopamine D3 receptor (Vogel et al 2004) were reported. A study has shown significantly higher mRNA levels for D3 receptor and lower for D4 receptor in T cells of schizophrenia patients (Boneberg et al 2006).…”
Section: T Cells As a Mediator Of Neuro-immune Interactions: Dopaminementioning
confidence: 95%
“…In the peripheral lymphocytes of schizophrenia patients, significantly increased mRNA expression of D2 and D3 receptors (Kwak et al 2001;Ilani et al 2001;Zvara et al 2005) and reduced gene expression of dopamine D3 receptor (Vogel et al 2004) were reported. A study has shown significantly higher mRNA levels for D3 receptor and lower for D4 receptor in T cells of schizophrenia patients (Boneberg et al 2006).…”
Section: T Cells As a Mediator Of Neuro-immune Interactions: Dopaminementioning
confidence: 95%
“…Later these cells were incubated with the virus at 37 • C for 2 h. The virus-containing medium was then decanted and replaced with fresh RPMI medium [17]. The infected cultures were sampled on either the third or the fourth day and the amount of virus produced was measured by p24 assay.…”
Section: Transient Transfection and Viral Infectionmentioning
confidence: 99%
“…Altered amyloid precursor protein (APP) mRNAs were quantified in PBMC from patients with Alzheimer's disease and Down's syndrome using the quantitative RT-PCR method (Ledoux et al, 1993(Ledoux et al, ,1995. Reduced dopamine receptor (D3) has been measured in lymphocytes from PD patients using HPLC and immunocytochemistry methods (Caronti et al, 1999), whereas increased levels of D3 dopamine receptor mRNA have been found in lymphocytes from schizophrenic patients using RT-PCR-ELISA assay (Ilani et al, 2001). Also, differences in myotonic dystrophy protein kinase (DMPK) gene expression has been determined in lymphocytes from patients with myotonic dystrophy and from normal controls, using a semi-quantitative RT-PCR radioactive assay (Depardon et al, 2001).…”
Section: Introductionmentioning
confidence: 99%